A xylan-degrading thermophilic and obligate anaerobe Xylanivirga thermophila gen. nov., sp. nov., isolated from an anammox dominant wastewater treatment plant, and proposal of Xylanivirgaceae fam. nov. (February 2020) - Liu, Lan; Lv, Ai-Ping; Ming, Yu-Zhen; Jiao, Jian-Yu; Xiao, Min; Lin, Jih-Gaw; Gu, Ji-Dong; Salam, Nimaichand; Li, Wen-Jun
Abstract: In our search for novel anaerobes with potential carbohydrate polymers degrading activity, we have isolated a xylan-degrading bacterial strain SYSU GA17129 T from an anammox bacteria dominant wastewater treatment plant. Phylogenetic analysis of the 16S rRNA gene sequence indicated the strain SYSU GA17129 T belong to the order Clostridiales and shared highest sequence identity with Caldicoprobacter faecalis DSM 20678 T (89.9%). The strain was thermophilic, obligately anaerobic, non-motile and rod shaped. Optimum growth of the strain was observed at 45 °C, pH 8.0 and in the presence of 0.5% NaCl (w/v). The chemotaxonomic features of the strain SYSU GA17129 T comprised of C14:0 FAME, iso-C15:0 FAME and C16:0 FAME as the major fatty acids (>10%), diphosphatidylglycerol, phosphatidylinositol mannoside, an unidentified phospholipid, three unidentified polar lipids and two unidentified glycolipids as its polar lipids, and meso -diaminopimelic acid ( meso -DAP) as the diamino acid in peptidoglycan. The G + C content of the genomic DNA was 35.9%. The strain could be distinguished from other defined families within the order Clostridiales by the differences in phenotypic and physiological characteristics, distinct phylogenetic lineage in 16S rRNA gene- and genome-based phylogenies and low genomic relatedness index. Based on these distinguishing properties, strain SYSU GA17129 T is proposed to represent a new species of a new genus Xylanivirga thermophila gen. nov., sp. nov., within a new family Xylanivirgaceae fam. nov. The type species of the new taxon is SYSU GA17129 T (=KCTC 15754 T = CGMCC 1.5282 T ). This strain is characterized within the order Clostridiales, class Clostridia of the phylum Firmicutes . Highlights: A xylan-degrading bacterial strain SYSU GA17129 T was isolated from a wastewater treatment plant. 16S rRNA gene and genome-based phylogenies reveal strain SYSU GA17129 T is a new member of the order Clostridiales . The strain is thermophilic, obligately anaerobic, non-motile and rod shaped.